Penggambaran Akuntan Forensik dan Teori Fraud dalam Film The Accountant - Ridho Dwinanda, Rizky; Agung Gde Satia Utama, Anak (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2025)
This study analyzes the depiction of fraud and forensic accounting in the film The Accountant, particularly through the lens of fraud theories like the Fraud Triangle and Fraud Diamond. The study applies fraud theories to illustrate how factors like pressure, opportunity, rationalization, ability, and integrity contribute to fraud. It also explores forensic accountants' role in detecting and preventing fraud. The research highlights the importance of psychological traits and ethical integrity in combating fraud, offering valuable insights for future research in forensic accounting, particularly regarding the interplay of psychology, technology, and collaboration in fraud prevention. The findings emphasize the role of forensic accountants in upholding moral standards even under significant pressure and opportunity for misconduct.